2009
DOI: 10.1007/s00253-009-1991-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of native isolates of lactic acid bacteria, bifidobacteria and yeasts for beneficial attributes

Abstract: In a changing scenario of food habits being associated with wellness factors through the concepts of probiotics and prebiotics, an attempt has been made to characterize on molecular basis, the desirable benefits associated with natural isolates of lactic acid bacteria, bifidobacteria, and yeasts. From a diverse range of foods and related samples, based on conventional microbiological protocols, three well-characterized natural isolates of Lactobacillus plantarum MTCC 5422, Bifidobacterium adolescentis MTCC 542… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The bacterial strain used in this study was L. plantarum (mtcc 5422) culture, isolated from fermented batter of cereal/legume (Roopashri & Varadaraj, 2009). All the glasswares used in this experiment were sterilized at 121°C for 15 min.…”
Section: Cell Culture Preparationmentioning
confidence: 99%
“…The bacterial strain used in this study was L. plantarum (mtcc 5422) culture, isolated from fermented batter of cereal/legume (Roopashri & Varadaraj, 2009). All the glasswares used in this experiment were sterilized at 121°C for 15 min.…”
Section: Cell Culture Preparationmentioning
confidence: 99%
“…The probiotic bacterial strain Lactobacillus plantarum (MTCC 5422), isolated from fermented batter of cereal/ legume (Roopashri and Varadaraj 2009) was used in this study. MRS broth, MRS agar, extra pure sodium chloride, methanol and bile salt were procured from HiMedia Laboratories, Mumbai, India.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we developed and validated a novel suicide gene therapy system by exploring the hypoxic environment of solid tumors and the anaerobic metabolism features of Bifidobacterium infantis bacterial cells. Our results have demonstrated that the Bifidobacterium infantis/thymidine kinase suicide gene therapy system may be used as a targeted cancer therapy [1-5]. …”
Section: Introductionmentioning
confidence: 99%